Fenomena Alih Fungsi Ruang Terbuka dan Trotoar oleh Pedagang Kaki Lima: (Studi Kasus: Kawasan Wisata Gunung Klotok, Kediri) - Fajarwati, Anisah Nur; Ramadhani, Suci Qadriana (Nature: National Academic Journal of Architecture, 2024)
The obstacle for pedestrians to carry out walking activities safely and comfortably on the sidewalk is something ironic. The artificial environment should be created to be able to carry out its functions and fulfill the rights of its users. Most of the conditions currently occurring are that the sidewalks are becoming narrower due to the presence of street vendors (PKL). This will continue to be a phenomenon and will always repeat itself because the existence of pedestrian paths cannot be separated from the existence of street vendors. This study aims to determine the phenomenon of conversion of open spaces and sidewalks by street vendors in the Gunung Klotok Forest Tourism Area. This research is qualitative research with descriptive and explanatory methods. The case study in this research is located in Kediri, especially the Mount Klotok Tourism Area. The results of this research conclude that the phenomenon of conversion of functions by the informal sector, both legal and illegal, can be observed in the Wana Wisata Gunung Klotok area. The lack of local government policy to organize areas, especially the informal sector, has resulted in many locations or places being converted to street vendors. Attention is needed from the management so that they can overcome the damage to the sidewalk which was originally planned as a pedestrian route but was displaced by selling activities. Another impact that arises from the conversion and change of location by illegal street vendors is that it appears that rubbish spots in the area have increased